POTENSI FESES TERNAK SAPI DALAM MENDUKUNG KEGIATAN PERTANIAN (Potential Cattle Feses in Support Agricultural Activity) - Irmayani Irmayani; Yusriadi Yusriadi; Arifuddin Arifuddin (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2017)
Abstract: Enrekang has approximately 2000 dairy cows were spread across several districts. If the average of the dairy cows produce feces every day as much as 35 kg, so the number of dairy cattle in the district waste Enrekang sebanyhak 70 tons / day. This fact shows the potential for waste is unbelievably big. The waste kepertingan if used for other sectors, such as agriculture, it will also create a promising organic farming. However, if waste is not utilized or dumped into the river or surrounding neighborhood residents, then a few years later would meet dairy cattle waste streams and neighborhoods. The method used for the libah memanfaatakan that use animal feces as a medium for the cultivation of worms, to support activities of livestock cattle feces dimanfaatakan as biogas, then the waste from the biogas is used also as a medium for the cultivation of worms. The results of the activities acquired two flagship products, the first worm which farmed in parentheses obtained within two months of worms doubled the number of sires. Second, the benefits obtained by the former media cultivation of worms into compost. Stool processing technology that diverse is expected to improve the knowledge of farmers in processing the waste so it is not wasted. Processing of pliers berfareasi feces will increase public interest in managing rancher sector so as to create farming systems based Zero Waste. Key Words : Potensi, Peternakan Sapi, Zero Waste